Pengembangan dan Implementasi Permainan Edukatif untuk Meningkatkan Kognitif, Sosial, dan Emosional Anak-Anak di Panti Asuhan Muhabbatul Haq - Zulaekha Preshanda, Zulaekha Preshanda; Nadia Martalata , Nadia Martalata; Rosdiana, Rosdiana; Sylvia Ardila Kurnia , Sylvia Ardila Kurnia; Jessica Shely , Jessica Shely; Cut Nabilah Insyirah , Cut Nabilah Insyirah; Puspita Bella , Puspita Bella; Kevin Novselvrin , Kevin Novselvrin; Vincent Kie , Vincent Kie; Jeremy Jones Halim, Jeremy Jones Halim; Tetti, Tetti; Eva Alya Putri, Eva Alya Putri; Farhan Sinatrya Cahyadi, Farhan Sinatrya Cahyadi; Zahra Naomi Faiza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate the effectiveness of a community service program through the development and implementation of educational games at Muhabbatul Haq Orphanage. The method used in this program involves three main stages: preparation and needs identification, educational game development, and game implementation. In the first stage, the team conducted initial observations and interviews with caregivers and children to identify their educational needs. The second stage involved the development and design of games that covered cognitive, social and emotional aspects. The third stage was the implementation of the games at the orphanage with regular game sessions. The results of the program showed significant improvements in the children's creativity and basic knowledge, as well as the strengthening of their social and emotional skills. The children were able to display creativity in the guessing game and answered questions well in the quiz, showing solid understanding. The program not only provides short-term benefits of improved knowledge and skills, but also long-term contributions to community development. In conclusion, educational games are proven to be effective in supporting children's development, building good character, and creating a fun learning environment.